Analysis Of Increasing Knowledge In The Making Of Local Micro Organisms (Mol) In Merigi Kelindang District Bengkulu Tengah - Miswarti Miswarti; Joko Santoso; Yulie Octavia; Wawan Eka Putra; Afrizon Afrizon; Yahumri Yahumri; Emlan Fauzi; Andi Ishak (UNIVED Press, Dehasen University Bengkulu, 2022)
The level of understanding of farmers in making MOL is very lacking, on the other hand, MOLes are needed to produce compost, plus farmers can make their own MOLes from materials that are around us. This study aims to determine the level of knowledge of farmers and students on the socialization of making MOL. The method used is a pre-test post-test one group design with a total of 44 respondents consisting of 26 farmers and 18 students who were determined purposively in January 2022. The increase in respondents' knowledge was tested using statistical paired sample t-test. The results of the implementation for farmers obtained that the correlation between pretest and posttest knowledge was positive at 0.154, significant at the =0.05 level, and for students at 0.657 indicating that the increase in post-test knowledge of socialization was not the same for every farmer and student. However, the level of knowledge of farmers on average increased from an average of 14.62% of students to an average of 19.44% due to socialization. Statistically, the level of knowledge of farmers and students increased significantly at the level of =0.05. This indicates that socialization is effective in increasing the knowledge of farmers and students in Kelindang Village, Merigi sub-district, Central Bengkulu Regency.